STUDI KOMPARATIF PEMIKIRAN JOHN RAWLS DAN MARTHA NUSSBAUM TENTANG KEADILAN SOSIAL - Indah, Astrid Veranita; Siola, Muhammad Natsir (Aqidah-Ta: Jurnal Ilmu Aqidah, 2025)
This research examines the philosophical thoughts of John Rawls and Martha Nussbaum on social justice through library research methods with a qualitative hermeneutic approach. The primary focus is to explore the concept of justice from both thinkers’ perspectives, analyze convergence and divergence points, and synthesize a comprehensive conceptual framework. The study compares four key domains: equality conception, resource distribution mechanisms, the state’s role, and the ethical dimensions of social life. Research findings demonstrate that social justice is a dynamic practice that transcends material distribution, emphasizing individual empowerment and human dignity recognition. Rawls offers a procedural approach through the original position, while Nussbaum focuses on core capabilities development. The synthesis of their thoughts produces a theoretical framework that promotes public policy transformation towards a more inclusive and just society.